Rancangan Aplikasi Rekomendasi Produk Skincare untuk Ibu Hamil Menggunakan Metode Prototype - Sri Wahyuni; Fajri Profesio Putra (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This research aims to develop an application for recommending safe and suitable skincare products for pregnant women. The application is built using the prototype method and implemented with the Python programming language using the Flask framework. The study encompasses product categories from Drw Skincare, including serums, toners, shampoos, body care products, facial washes, and creams. The system provides options for users to select categories of skincare ingredients they desire. The application issues warnings about skincare ingredients that should be avoided during pregnancy, such as retinol and specific acids. The end result is a list of recommended skincare products containing ingredients that align with the user's selected criteria. Each product is accompanied by comprehensive information about its ingredients and advice. Users can utilize search and advanced filtering features to find skincare products based on product types and brands. The application offers clear user guidance and an intuitive interface, enabling users to navigate and use the application comfortably. It is expected that this application can assist pregnant women in choosing safe and effective skincare products while providing a better understanding of skincare during pregnancy.